The Role of Halal Certification in Increasing the Interest of Muslim Consumers in Halal Tourism Destinations - Primadona, Fitry; irwandar, Sapta N; Hartoyo, Hartoyo; Yuliati, Lilik Noor; Arsyianti, Laily Dwi (Adpebi Science Series, 2024)
This research examines the role of halal certification in increasing the interest of Muslim consumers in halal tourismdestinations. Through a qualitative literature review approach, this study explores the impact of halal certification onthe perceptions and preferences of Muslim consumers in choosing halal tourism destinations. Analysis of variousliterature sources reveals that halal certification plays a crucial role in building trust and confidence among Muslimconsumers regarding the products and services offered in the context of tourism. It is also found that halal certificationcan enhance the image and attractiveness of halal tourism destinations, as well as provide assurance to Muslimconsumers regarding the fulfillment of religious needs and regulations during their travels. The practical implicationsof this research support the importance of halal certification as a marketing strategy in attracting Muslim consumersto visit halal tourism destinations. In conclusion, this study provides valuable insights for the tourism industry andhalal certification organizations in understanding the dynamics of the market and the needs of Muslim consumers inthe context of halal tourism.